2019
DOI: 10.1136/bmjopen-2019-032904
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with frailty among community-dwelling older people in rural Thanjavur district of South India: a cross-sectional study

Abstract: ObjectiveThere is sparse data on the prevalence of frailty from rural parts of India. Our aim was to estimate prevalence of frailty among community-dwelling older people in rural South Indian population and explore socio-demographic factors associated with frailty. We further explored the associations between frailty with fear of falling and falls.DesignCommunity based cross-sectional study.SettingFour villages in Thanjavur district of Southern India.ParticipantsRandom sample of adults aged 60 years and above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
53
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 41 publications
13
53
3
Order By: Relevance
“…The prevalence in less developed countries such as Sri Lanka, Vietnam, Indonesia and India were 15.2%, 21.7%, 25.2% and 28.0%, respectively [15][16][17][18], which were higher than the present study. The present study also identified a very similar prevalence rate to previously reported in two provinces of northern Thailand, which was a 15.0% frailty prevalence [10].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The prevalence in less developed countries such as Sri Lanka, Vietnam, Indonesia and India were 15.2%, 21.7%, 25.2% and 28.0%, respectively [15][16][17][18], which were higher than the present study. The present study also identified a very similar prevalence rate to previously reported in two provinces of northern Thailand, which was a 15.0% frailty prevalence [10].…”
Section: Discussioncontrasting
confidence: 83%
“…In more developed countries, these factors include age, black race, female gender, cardiovascular disease, number of comorbidities, functional incapacity, poor self-rated health, depressive symptoms, body mass index, smoking, low schooling level, low income, poor cognitive function and alcohol consumption [2,[11][12][13][14]. In less developed countries, these factors include age, female gender, lower education, longest-held occupation, lower socioeconomic status, low physical activity, comorbidities, functional status and nutritional status [15][16][17][18]. In summary, factors associated with geriatric frailty fall into the following domains: socio-demographic, physical, psychological, functional, and lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…We found that most people in old age groups were susceptible to frailty, and at higher risk of medical conditions than pre-elderly age group, which is consistent with previous studies [1,4,27,43,44]. Lanka is consistent with our study ndings [14,18,20,45].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, frailty indices consider various aspects of general health assessment including self-reported medical history, biomarkers and performance in daily activities. Gender was identi ed as a risk factor for predicting the older adults' frailty [14,27]. This study's ndings agree on previous studies in reporting that female older adults in low-income countries, South Asia in particular, are generally reluctant about their health complexities and they do not take proper initiatives for health check-ups [27,[54][55][56].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation